Catalytic Epoxidation and syn-Dihydroxylation Reactions in Steroid Chemistry - Salvador, Jorge A.R.; Silvestre, Samuel M.; Moreira, Vania M. (Current Organic Chemistry, 2008)
The oxidation of steroidal olefins allows the incorporation of functional groups into their skeleton and accounts for the obtention of valuable intermediates in the synthesis of pharmaceuticals, agrochemical and other fine chemicals. The catalytic epoxidation and syn-dihydroxylation reactions of steroidal alkenes are reviewed.